Perspectives in renal replacement therapy: Haemodialysis. (8th October 2018) - Liew, Adrian
ABSTRACT: Haemodialysis (HD) was the first procedure that had demonstrated the ability to partially replace renal function, and became the most widely utilized treatment for patients with end‐stage renal disease (ESRD). In a great majority of countries around the world, conventional in‐centre HD had become the predominant renal replacement therapy, being touted as able to achieve better solute clearance and more successful in attaining euvolemia than patients on peritoneal dialysis. This is despite the antecedent hemodynamic risks, more rapid loss of residual renal function, greater infectious perils, excessive erythropoietin requirements and higher infrastructure costs. In addition, quality of life had been suggested to be worse among patients on HD, though this had been challenged repeatedly. Consequently, the concept of integrated ESRD care over the last few decades had placed HD, as a complementary rather than a competitive treatment modality to the entire armamentarium of renal replacement therapies. Incorporating HD as part of integrated care into health‐care policies and national resource planning will become an essential strategy in improving access and outcome to care among the ESRD population. The improvement in technologies and innovation in prescription had brought forth enhanced dialyzer membrane and machine upgrades, and expanded modalities including more frequent HD and haemodiafiltration. While boasting of controversial improvement in outcomes, many of these therapies remain expensive and insurmountable for widespread utility in many countries. In addition, the results of these new technologies had been conflicting across studies, with some even suggesting that they could be detrimental. Therefore, judicial consideration has to be undertaken to appropriate their use in clinical practice. Summary at a Glance: The article reviews the recent advances in haemodialysis technology and their relevance to current clinical practice.